Jum'ul Al Quran, Dalam Perspektif Sejarah Islam - Muhammad Ikrom; Tsaniah Marta; Nia Ramadhani; Hakmi Hidayat (GLOBAL SCIENTS PUBLISHER, 2025)
The Qur'an is a revelation from Allah SWT that was revealed to the Prophet Muhammad SAW gradually over a period of 23 years. The collection and codification of the Qur'an has a very important role in maintaining its authenticity so that it remains protected from change. The process of collecting the Qur'an began during the time of the Prophet Muhammad SAW with memorization by his companions and recording on various media such as date palm stems, animal skins, and camel bones. After the Prophet's death, during the time of Caliph Abu Bakr Ash-Shiddiq, the Qur'an was collected into one mushaf to avoid losing the revelation due to the death of the memorizers in the Riddah War. Furthermore, during the time of Caliph Uthman bin Affan, differences in reading among Muslims caused by differences in dialect were finally standardized by making several copies of the official mushaf and burning other mushafs with different readings. This process continues with developments in writing, adding punctuation, and systematics that make it easier to read the Qur'an. The study of Jum‘ul Qur'an is very important in understanding how these efforts have maintained the authenticity and purity of the Qur'an until today.